Use of simulation in the industry 4.0 context: Creation of a Digital Twin to optimise decision making on non-automated process. Issue 3 (4th May 2022) - Santos, Carlos Henrique dos; de Queiroz, José Antônio; Leal, Fabiano; Montevechi, José Arnaldo Barra
ABSTRACT: The advent of new technologies brings a significant impact on systems management. The Industry 4.0 looks for increasingly automated, integrated, and digitised processes. We highlight the use of simulation as a Digital Twin, a virtual and intelligent copy capable of mirroring real processes and optimise decision making. This paper analyses the applicability of the Discrete Event Simulation as a Digital Twin in a non-automated process, a challenging scenario on the implementation of Industry 4.0 solutions. Amethod for conducting simulation projects of this nature was proposed, considering its integration with the process data, as well as its constant updating due to changes in the real environment. To verify its applicability, the method was used in a real study object. The proposed approach proved possible from the present research. We also present some discussions related to the use of simulation as Digital Twins, highlighting the main characteristics of such an application.